HUBUNGAN KEAKTIFAN IBU DALAM KEGIATAN POSYANDU DENGAN STATUS GIZI PADA ANAK BALITA DI DESA PENTADIO BARAT KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Fitri Yani Arbie; Salmaningsih Moputi (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2016)
ABSTRACT The activity of the mother at each posyandu activity will certainly affect the nutritional status of her toddler child. Because one of the purposes of the Posyandu is to monitor the improvement of the nutritional status of the community, especially children under five and pregnant women. There is also the Research Objective, is to Know the Relationship of the Activity of Mothers in Posyandu Activities with Nutritional Status of Toddler Children in Pentadi Barat Village, Telaga Biaru District, Gorontalo Regency.Research Method, This type of research is an analytical survey with a cross sectional study design, and the population in this study were 352 people by getting a sample of as many as 79 people.As for the Research Results the level of activity of mothers in the posyandu activities included in the active category was only 17 people (21.5%), and those included in the inactive category were 62 people (78.5%), and the results of the study were categorized as good nutritional status there were 52 people (65.8%), and those included in the category of malnutrition status were 27 people (34.2%).The conclusion of this research after chi-square testing is that there are indigo x2 count